Pengembangan Sistem Pendeteksi Kehadiran Pegawai Berbasis Fingerprint Wifi - Rizky Haryandi Rahman; Adhitya Bhawiyuga; Primantara Hari Trisnawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Checking the employees attendance is an important matter for every institution or company to see their own employee performance. Each instituion or company must have their own way to check the employees attendance, such as using a paper, smartphone application, RFID (Radio Frequency Identification), and biomentric technique. Those kind of ways are really making the company easier to check the employees attendance, but there is a flaw, for example is on the fingerprinting system when using the fingerprint, sometimes the fingerprint can not be detected by the system, moreover an employee should reach a specific location to make a presence. This sometimes make the employees to procrastinate or late to make a presence. As a result, the employees often forget and do not make a presence. From the problem, this reasearch is made to make a presence system for employees using a wifi fingerprint, wifi fingerprint means a MAC address which is caught by microtic router when a smartphone is connected. System will read the MAC address and interface of the router mikrotik through the API for RouterOS, then save it into the database, and compare it with the MAC address already in the database, so when it happens, an employee will be considered as present and the location of an employee will be known based on a place where a smartphone is connected. The testing result of functionality and performance shows the all functions on system run well and the time that needed by a system to read from a router has an average below of one second and the time for system to detect the presence including the employees location is about five seconds.